2009
DOI: 10.1007/s10549-009-0523-x
|View full text |Cite
|
Sign up to set email alerts
|

A randomized trial exploring the biomarker effects of neoadjuvant sequential treatment with exemestane and anastrozole in post-menopausal women with hormone receptor-positive breast cancer

Abstract: Several adjuvant endocrine strategies exist for postmenopausal women with breast cancer. This study compared the effect of two sequences of aromatase inhibitor use [steroidal (exemestane) and non-steroidal (anastrozole)] on serological and pathological biomarkers when given in the neoadjuvant setting to postmenopausal women with breast cancer. Thirty women were assigned to receive exemestane 25 mg or anastrozole 1 mg each given for 8 weeks in a randomized sequence. The effect of this treatment on serum estrone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 19 publications
1
8
0
Order By: Relevance
“…In the present study, an in‐depth SH profile comparing third‐generation AIs showed that levels of all the measured hormones were significantly higher in the exemestane group. Previously, studies have predominantly involved one of these AIs alone, reporting changes before and after treatment for oestradiol, oestrone and oestrone sulphate, or have been crossover studies with all but one comparing anastrozole and letrozole. A previous report showed that after 8 weeks of treatment with exemestane, 69 per cent of women had complete suppression of oestradiol, compared with 78 per cent of those who received anastrozole; the present findings are in line with these results.…”
Section: Discussionsupporting
confidence: 88%
“…In the present study, an in‐depth SH profile comparing third‐generation AIs showed that levels of all the measured hormones were significantly higher in the exemestane group. Previously, studies have predominantly involved one of these AIs alone, reporting changes before and after treatment for oestradiol, oestrone and oestrone sulphate, or have been crossover studies with all but one comparing anastrozole and letrozole. A previous report showed that after 8 weeks of treatment with exemestane, 69 per cent of women had complete suppression of oestradiol, compared with 78 per cent of those who received anastrozole; the present findings are in line with these results.…”
Section: Discussionsupporting
confidence: 88%
“…Changes in tumor Ki67 expression is a well-recognized surrogate endpoint for treatment response [ 18 – 21 ] and predictor of clinical outcome [ 22 , 23 ]. Variability in Ki67 staining can occur as a result of a number of factors, including the duration of tissue ischemia, formalin quality, duration of fixation, immunohistochemical technique used, and assessor differences.…”
Section: Discussionmentioning
confidence: 99%
“…Results indicated that the greatest suppression was observed in patients taking letrozole, and the least suppression was with exemestane. 55,56 Importantly, a prospective randomized, trial (MA.27) comparing anastrozole and exemestane demonstrated no difference in DFS or OS in the adjuvant setting. 57 The superiority of letrozole compared to the other AIs, in terms of long-term clinical outcomes, has not been established.…”
Section: Neoadjuvant Endocrine Therapymentioning
confidence: 99%